Mathematics Teacher’s Beliefs and Practices towards Collaborative Learning - Maria Shiraz; Shahzada Qaisar (The Journal of Humanities & Social Sciences, 2021)
This paper has been drawn from the findings of a larger study which explores a mathematics teacher’s practices who believes in the use of collaborative learning (CL). It also attempts to identify the extent of consistency between the teacher’s beliefs and his practices. Data was collected through questionnaires and classroom observations. The analysis of the questionnaire helped to differentiate the teachers who believed in collaborative learning. The results of the video data showed the extent of alignment of the teacher’s beliefs with the patterns of his practices. Analysis of observational data revealed inconsistencies in the practices and beliefs of the teacher towards the use of collaborative learning. The findings of the present study indicated that the teacher seemed unaware in the effective implementation of CL. The nature of the belief- practice relationship amongst mathematics teachers is complex and mediated by external factors.